Návrh rozvoje podnikatelského konceptu restaurace HAN FOOD - Le, Kim Thu (Vysoké učení technické v Brně. Fakulta podnikatelská, 2021)
Cílem této bakalářské práce je návrh rozvoje fast casual konceptu HAN FOOD v Praze. Pro splnění vytčeného cíle byla nejdříve zpracována literární rešerše k dané oblasti, následně realizována analýza stávajícího provozu, a to pomocí metod SLEPTE, analýzy konkurenčních sil dle Portera a McKinseyovy analýzy „7S“. Výstupy byly shrnuty pomocí SWOT. Na základě zjištěné situace bylo přikročeno k návrhům, které přispějí k rozvoji.

The objective of this bachelor thesis is to propose the development of the fast casual concept HAN FOOD in Prague. In order to meet the objective, relevant literature review had been conducted, followed by analysis of existing operations using SLEPTE methodology, Porter’s competitive forces analysis and McKinsey’s “7S” model. The findings were summarized using SWOT analysis. Based on the identified results, the proposals that contribute to development have been recommended.
Proposal for the BusinessDevelopment of the HAN FOOD restaurant.
Keywords: podnik; podnikatelský plán; strategie; analýza podniku; rozvoj; Business; business plan; strategy; business analysis; developement